Effectiveness of Differentiated Instruction in Teaching Mathematics for Grade Three Pupils - Cornelio, Ronalyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of differentiated instruction in teaching Mathematics among Grade Three pupils at Baras Elementary School during the School Year 2025–2026. The research employed an experimental design, specifically a single-group pretest–posttest approach, involving thirty (30) Grade Three pupils. The respondents were described in terms of sex, sibling position, number of children in the family, parents’ educational attainment, parents’ occupation, and monthly family income. A researcher-made test was utilized to measure pupils’ performance before and after the implementation of differentiated instruction.Findings revealed that most of the pupils were male, first-born, belonging to families with two children, and had parents who were college graduates employed in government positions with a monthly income of ₱20,000 and above. In terms of Mathematics performance, pupils initially obtained a rating of “Did Not Meet Expectations” in the pretest, particularly in competencies such as understanding and visualization of measurement conversion, application in problem solving, representation of measures, and integration across measurement types. However, after exposure to differentiated instruction, their performance significantly improved to a “Very Satisfactory” level in the posttest results. Statistical analysis showed a significant difference between pretest and posttest scores, indicating the effectiveness of differentiated instruction.Further analysis revealed that no significant differences existed in pupils’ posttest performance when grouped according to sex, sibling position, parents’ educational attainment, parents’ occupation, and monthly family income. However, a significant difference was observed when pupils were grouped according to the number of children in the family, suggesting its influence on learning outcomes.The study concluded that differentiated instruction is effective in improving pupils’ Mathematics performance. It is recommended that teachers continue implementing differentiated strategies, while school administrators provide continuous professional development and monitoring to sustain instructional effectiveness. Further studies may be conducted to explore additional variables affecting the impact of differentiated instruction.